Ethical dilemma encountered during the recruiting process : perceptions of accounting and engineering majors, and recruiters. - Liang, Chan Hoe. (2008)
Ethics is highly valued by the business world, the accounting profession and the accounting education. Our paper extends the study of ethics in a relatively new context, the recruiting process. We examine the ethical perceptions of recruiters and graduating students in both accountancy and engineering. The ethical perceptions of the subjects were captured via six cases focusing on dilemmas encountered in the job search process.